Artificial neural network modelling for the prediction of carbon surface area - Abd. Razak, Norhuda (2004)
Carbon nanotubes are considered for hydrogen storage due to their low density, high strength, and hydrogen adsorption characteristics. Recent reports suggest that total surface area of carbon nanotubes affect the hydrogen storage capacities in carbon nanotubes. An Artificial Neural Network model has been created for the prediction of the surface area of carbon. The model is used to study the influence of the different type of carbon on the hydrogen storage properties of carbon nanotubes.